2017
DOI: 10.1016/j.surfcoat.2016.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and abrasive wear behaviour of Al-based PVD amorphous/nanostructured coatings

Abstract: Article:Lawal, J., Kiryukhantsev-Korneev, P., Matthews, A. et Compositional analysis of AlNiTiSiB(N) coatings was carried out by glow discharge optical emission spectroscopy (GDOES). Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) were used to study the structure of the coatings; hardnesses and elastic moduli were also determined. The abrasive wear behaviour of the coating-substrate system was studied using a slurry micro-abrasion wear test. Nitrogenfree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
0
7
0
1
Order By: Relevance
“…The tribological test of TiAlN, TiAlSiN, CrN/TiAlCrSiN and CrN/CrCN/DLC coatings showed that no correlation between H/E or H 3 /E 2 ratio and the wear resistance [148]. Similarly, the tests of TiAlN(Ag,Cu) and AlNiTiSiB(N) coatings did not confirm this relationship [135,149]. Lack of such correlation was also noted in Ref [134].…”
Section: Resistance Of Pvd Coatings To Wearmentioning
confidence: 92%
“…The tribological test of TiAlN, TiAlSiN, CrN/TiAlCrSiN and CrN/CrCN/DLC coatings showed that no correlation between H/E or H 3 /E 2 ratio and the wear resistance [148]. Similarly, the tests of TiAlN(Ag,Cu) and AlNiTiSiB(N) coatings did not confirm this relationship [135,149]. Lack of such correlation was also noted in Ref [134].…”
Section: Resistance Of Pvd Coatings To Wearmentioning
confidence: 92%
“…The development of protective coatings using different techniques such as PVD (Lawal, et al, 2017), CVD (Köpf, et al, 2017), solid liquid vapor (VLS) method (Klamchuen, 2015), among others has allowed solving problems associated with tool corrosion, friction torques and wear (Kameneva & Kichigin, 2019). However, with the rapid progress of the doi: https://doi.org/10.18257/raccefyn.1198 Rev.…”
Section: Introductionmentioning
confidence: 99%
“…ZrB 2 -based coatings can be produced by a wide variety of techniques, including plasma deposition [21][22][23], diffusion saturation [24], salt electrolysis [25], electrospark deposition [26,27], chemical vapor deposition [28] and arc-PVD [29]. Magnetron sputtering offers several advantages, including low surface roughness, substrate geometry retention [30,31], low content of pores and structural defects [32,33], high adhesion to the substrate when the preliminary ion etching is applied [34][35][36], precise control of the structural characteristics via the adjustment of the sputtering parameters [37], the versatility of the used substrates [38][39][40][41] and uniform depth-wise distribution of the elements in the multi-element coatings [41][42][43].…”
Section: Introductionmentioning
confidence: 99%